2012
DOI: 10.1089/fpd.2011.1018
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Molecular Characterization, and Antibiotic Susceptibility ofVibrio parahaemolyticusin Korean Seafood

Abstract: The principal objective of this study was to investigate the incidence, risk assessment, antibiotic resistance, and genotyping of Vibrio parahaemolyticus in Korean seafood. The incidence of V. parahaemolyticus in seafood obtained from several fish markets in Korea was investigated from May to December of 2009, except between July and September. Two selective mediums (TCBS [thiosulfate, citrate, bile salts, and sucrose] agar and CHROMagar™ Vibrio) were used, and the V. parahaemolyticus strains were identified v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 32 publications
(36 reference statements)
4
42
0
Order By: Relevance
“…This result suggests that these drugs can be used as an alternative antibiotic therapy. It must be noted that recently isolated V. parahaemolyticus strains, including pandemic strains, have displayed resistance to multiple antibiotics (Jun et al, 2012, 2014), which increases concerns about possible antibiotic treatment failure. Although we did not discover any multidrug resistant bacteria (MDR) isolates in this study, continued monitoring of pandemic strain susceptibility to antibiotic resistance is urgently needed to avoid the excessive misuse of antibiotics used to treat infections that pose threats to public health.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that these drugs can be used as an alternative antibiotic therapy. It must be noted that recently isolated V. parahaemolyticus strains, including pandemic strains, have displayed resistance to multiple antibiotics (Jun et al, 2012, 2014), which increases concerns about possible antibiotic treatment failure. Although we did not discover any multidrug resistant bacteria (MDR) isolates in this study, continued monitoring of pandemic strain susceptibility to antibiotic resistance is urgently needed to avoid the excessive misuse of antibiotics used to treat infections that pose threats to public health.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, V. parahaemolyticus SNUVpS-1 was isolated from seafood (corb shell, Cyclina sinensis ) from a fishery market in Seoul, Republic of Korea (4). It contained the thermolabile hemolysin gene (TL gene), the V. parahaemolyticus toxR gene, and the toxRS sequence of the O3:K6 clone isolated before 1995 ( toxRS old ) (4). In addition, it evidenced multiple-antibiotic resistance and was found to contain the antibiotic-resistance genes tetA and strB (4).…”
Section: Genome Announcementmentioning
confidence: 98%
“…V. parahaemolyticus is recognized globally as an important human pathogen (13). V. parahaemolyticus pandemic strains, such as O3:K6, contain a unique toxRS sequence that is associated with the current pandemic (4, 5). Increasingly, there have been reports of antibiotic resistance in Vibrio species.…”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…[28]; who studied S. boydii infection cases from 2002 to 2003, reported that all the strains were resistant to trimethoprim-sulfamethoxazole and all except one strain were resistant to streptomycinsolation which are commonly used in the treatment of shigellosis. Emergence of antibiotic resistance which causes serious clinical problems in the treatment has made the development of alternatives to conventional antibiotics a top priority [19,24].…”
Section: Introductionmentioning
confidence: 99%